Grp78 Is Critical for Amelogenin‐Induced Cell Migration in a Multipotent Clonal Human Periodontal Ligament Cell Line. Issue 2 (February 2016) - Toyoda, Kyosuke; Fukuda, Takao; Sanui, Terukazu; Tanaka, Urara; Yamamichi, Kensuke; Atomura, Ryo; Maeda, Hidefumi; Tomokiyo, Atsushi; Taketomi, Takaharu; Uchiumi, Takeshi; Nishimura, Fusanori
<x xml:space="preserve">Abstract</x> Periodontal ligament stem cells (PDLSCs) are known to play a pivotal role in regenerating the periodontium. Amelogenin, which belongs to a family of extracellular matrix (ECM) proteins, is a potential bioactive molecule for periodontal regenerative therapy. However, its downstream target molecules and/or signaling patterns are still unknown. Our recent proteomic study identified glucose‐regulated protein 78 (Grp78) as a new amelogenin‐binding protein. In this study, we demonstrate, for the first time, the cellular responses induced by the biological interaction between amelogenin and Grp78 in the human undifferentiated PDL cell line 1‐17, which possesses the most typical characteristics of PDLSCs. Confocal co‐localization experiments revealed the internalization of recombinant amelogenin (rM180) via binding to cell surface Grp78, and the endocytosis was inhibited by the silencing of Grp78 in 1‐17 cells. Microarray analysis indicated that rM180 and Grp78 regulate the expression profiles of cell migration‐associated genes in 1‐17 cells. Moreover, Grp78 overexpression enhanced rM180‐induced cell migration and adhesion without affecting cell proliferation, while silencing of Grp78 diminished these activities. Finally, binding of rM180 to Grp78 promoted the formation of lamellipodia, and the simultaneous activation of Rac1 was also demonstrated by NSC23766, a widely accepted Rac1 inhibitor. These results suggest that Grp78 is essential for enhancing amelogenin‐induced migration in 1‐17 cells. The biological interaction of amelogenin with Grp78 offers significant therapeutic potential for understanding the biological components and specific functions involved in the signal transduction of amelogenin‐induced periodontal tissue regeneration. J. Cell. Physiol. 231: 414–427, 2016. © 2015 Wiley Periodicals, Inc.